HALAL CERTIFICATION PROCEDURE IN MALAYSIA AND INDONESIA - Johari Ab Latiff (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2020)
Pharmaceutical products deals with different component of materials or substances and its whole process are more critical than food products. Malaysia has launched and implemented the Malaysian Standard MS 2424:2012 Halal Pharmaceuticals-General Guidelines since 2012 on halal pharmaceuticals and to the pharmaceutical manufacturers. The government of Indonesia also making halal labelling on all products mandatory in Indonesia by 2019. This momentum of halal certification for pharmaceutical products by both countries need to be enhance by improving the initiatives the implementation of standard and guidelines. The objectives of the study are to explain the concept of halal pharmaceuticals based on halal certification procedure in Malaysia and Indonesia, to examining the evidence from the Holy Al-Quran, as-Sunnah and dalil due to the determination of halal pharmaceuticals products, to analyse general principles based on Islamic law to the determination of halal pharmaceutical products and to identify a new method based on Islamic principles in determining the halal pharmaceutical products. In general, the qualitative method is used in this study, the data collection methods are through document analysis. The findings of this study. First, in understanding the concept of halal pharmaceuticals in Malaysia and Indonesia it is basically not only based on Islamic law alone, but also subject to the criteria and regulations enforced in both countries. Second, the Islamic principle of halal and haram, darurah and fatwa is a basis or general Islamic principle applicable to determine halal pharmaceuticals products. Third, the comprehensive method or criteria for determination of halal pharmaceutical products is encompassing the principle of pharmaceuticals derived from halal substances, materials, the principle of Maslahah, the principle of Ihtiyathand the principle of Istihalah Tammah. Abstrak: Produk farmasi berkaitan dengan komponen bahan atau zat yang berbeda dan seluruh prosesnya lebih penting daripada produk makanan. Malaysia telah meluncurkan dan menerapkan Standar Malaysia MS 2424:2012 Pedoman Umum Farmasi Halal sejak 2012 tentang obat-obatan halal dan kepada produsen farmasi. Pemerintah Indonesia juga mewajibkan pelabelan halal pada semua produk di Indonesia pada 2019. Momentum sertifikasi halal untuk produk farmasi oleh kedua negara perlu ditingkatkan dengan meningkatkan inisiatif penerapan standar dan pedoman. Penelitian ini bertujuan untuk menjelaskan konsep kehalalan obat berdasarkan prosedur sertifikasi halal di Malaysia dan Indonesia, mengkaji dalil-dalil dari Al-Qur'an, As-Sunnah dan dalil karena penentuan produk obat halal, menganalisis prinsip-prinsip umum berdasarkan hukum Islam untuk penentuan produk farmasi halal dan untuk mengidentifikasi metode baru berdasarkan prinsip-prinsip Islam dalam menentukan produk farmasi halal. Artikel ini menggunakan metode penelitian kualitatif, dengan metode pengumpulan datanya melalui analisis dokumen. Temuan dalam artikel ini adalah, pertama, dalam memahami konsep kehalalan farmasi di Malaysia dan Indonesia pada dasarnya tidak hanya berdasarkan syariat Islam saja, tetapi juga tunduk pada kriteria dan peraturan yang berlaku di kedua negara. Kedua, syariat Islam tentang halal dan haram, darurah dan fatwa merupakan dasar atau prinsip umum Islam yang berlaku untuk menentukan kehalalan produk farmasi. Ketiga, metode atau kriteria yang komprehensif dalam penetapan kehalalan produk farmasi meliputi prinsip kehalalan obat yang berasal dari zat, bahan, prinsip mashlahah, prinsip ihtiyath dan prinsip istihalah tammah. Kata Kunci: Sertifikasi Halal, Penetapan Farmasi, Produk Halal di Malaysia dan Indonesia